High-order Analysis of Linear Vibrations of a ModeratleyThick Sandwich Panel With an Electrorheological Core - Mehdi Keshavarzian; Mohammad Mehdi Najafizadeh; Korosh Khorshidi; Peyman Yousefi; Majid Alavi (Mechanics of Advanced Composite Structures)
In this study, the frequency response of rectangular sandwich plates with multi-layer face sheets and electrorheological (ER) fluid cores is investigated. The assumed electro-rheological fluid as a core is capable of changing the stiffness and damping of structures. In modelling the sandwich panel implemented for the first time, first-order shear deformation theory and the second Frostig's model are applied for the face sheets and thick cores, respectively. The sandwich panel under study is supposed to simply support boundary in all edges, and the Galerkin approach is implemented for discretizing the problem. In the result section, impacts of various parameters such as electric field, aspect ratio, the thickness of the ER layer, and thickness ratio on vibrational characteristics of the structure are discussed in detail.  The obtained results highlight the notable effects of the electric field on natural frequencies, which can make the structure flexible within the desired range. It is also pointed out that the dynamic behavior and stability of the system can be controlled by changing the magnitude of the ER fluid layer.